Tek ve çift kat UV vernik sistemi uygulanmış parkelerde renk ve parlaklık değerlerinin belirlenmesi - Gürleye, Tuğba; Ayata, Ümit; Gürleyen, Levent; Esteves, Bruno; Sivrikaya, Hüseyin; Can, Ahmet; Sivrikaya, Hüseyin; Can, Ahmet (2nd International Conference on Material Science and Technology in Cappadocia, 2017)
In this study the determination of the color and glossiness values on the parquets which underwent a UV varnishing treatment according to different varnish layers that are produced from, limba, sapelli, chestnut and iroko was aimed. As a result of this; the color and glossiness values were determined on the derived samples which had different layers. Taking all these results into consideration the highest total color difference value (?E*) was determined to be on iroko samples which underwent a single layer UV varnishing treatment, the highest perpendicular and parallel to grains glossiness value was determined to be on limba samples which underwent double layer UV varnishing treatment, the highest lightness value (L*) was determined to be on the control samples of limba wood, the highest red color (a*) was determined to be on sapelli samples which underwent double layer UV varnishing treatment and the highest yellow color (b*) was determined to be on iroko samples which underwent a single layer UV varnishing treatment. In view of their anatomical structures, the wooden materials were detected to have different total color difference (?E*) values after UV system varnish application. As a consequence; the glossiness level was detected to be higher on limba wood on which double-coated UV varnish was applied, whereas the total color difference (?E*) was detected to be higher on iroko wood on which one-coat UV varnish was applied.

Bu çalışmada, limba, sapelli, kestane ve iroko odunlarından üretilen farklı vernik katmanlarına göre UV vernik uygulanmış parkeler üzerinde; renk ve parlaklık değerlerinin belirlenmesi amaçlanmıştır. Bu amaçla, elde edilen farklı katmanlardaki deney örnekleriüzerinde renk ve parlaklık ölçümleri belirlenmiştir. Bu sonuçlara göre, en yüksek toplam renk farkı (?E*) değeri tek kat UV vernik uygulanmış iroko örneklerinde, en yüksek yüzeye dik ve paralel parlaklık değeri çift kat UV vernik uygulanmış limba örneklerinde, en yüksek ışıklılık (L*) değeri limba odununun kontrol örneklerinde, en yüksek kırmızı renk (a*) değeri çift kat UV vernik uygulanmış sapelli örneklerinde ve en yüksek sarı renk (b*) değeri ise tek kat UV vernik uygulanmış iroko örneklerinde tespit edilmiştir. Ahşap malzemelerin anatomik yapılarından ötürü UV sistem vernik uygulaması sonrasında toplam renk farkı (?E*) değerlerinin farklı çıktığı tespit edilmiştir. Sonuç olarak; parlaklık derecesinin çift kat UV vernik uygulanmış limba odununda, toplamrenk farkının ise tek kat uygulanmış iroko odununda yüksek çıktığı ortaya çıkmıştır
Keywords: Parquet, UV varnish system, Color, Glossiness; Parquet; UV varnish system; Color; Glossiness; Parke; UV vernik sistemi; Renk; Parlaklık